International Maritime Organization's Resolution on the Interpretation of the Breaking the Right to Limit Liability - Comert, Venus; Süzel, Cüneyt (Ankara Üniversitesi Deniz Hukuku Ulusal Araştırma Merkezi, 2022)
The shipowner’s liability is limited for claims set out in Article 2 of the Convention on Limitation of Liability for Maritime Claims, 1976 and the Protocol of 1996 to Amend the Convention on Limitation of Liability for Maritime Claims, 1976 and for claims regarding oil pollution from a tanker pursuant to the International Convention on Civil Liability for Oil Pollution Damage, 1992. Limitation of liability provisions shall not be applied in case the level of culpability stipulated in the relevant articles of the Conventions is proven. By way of its three decisions dated 15/12/2021, the International Maritime Organisation (IMO) has adopted common interpretation rules including the other conventions providing similar regulations to ensure that the level of culpability expressed as “wilful conduct” shall be interpreted in a uniform manner by the State Parties and courts of the State Parties. This article evaluates the IMO’s decision regarding the common interpretation of Article 4 of the Convention on Limitation of Liability, 1976 by examining the travaux préparatoires of the Convention, the level of culpability stipulated in the Conventions and the effect of wilful misconduct on insurance contracts.

Deniz Alacaklarına Karşı Mesuliyetin Sınırlanması Hakkında 1976 Tarihli Milletlerarası Sözleşme ve onu tadil eden 1996 Sınırlı Sorumluluk Protokolü uyarınca Sözleşmenin 2’nci maddesinde yer verilen istemler ve 1992 Petrol Kirliliğinden Doğan Zararın Hukuki Sorumluluğu ile İlgili Milletlerarası Sözleşme uyarınca tankerden kaynaklanan petrol kirliliğine ilişkin istemler için sorumluluk sınırlandırılmaktadır. Sözleşmelerde öngörülen sorumluluk sınırları Sözleşmelerin ilgili maddelerinde düzenlenen kusur derecesinin ispatlanması hâlinde uygulanmayacaktır. Uluslararası Denizcilik Örgütü (IMO) tarafından 15/12/2021 tarihli üç Karar ile taraf devletler ve taraf devlet mahkemeleri tarafından özellikle “pervasızca davranış” olarak ifade edilen kusur derecesinin aynı şekilde yorumlanmasını sağlamak amacıyla benzer düzenlemelerin yer aldığı Milletlerarası Sözleşmeleri de kapsayacak nitelikte ortak yorum kuralları getirilmiştir. Çalışmada IMO tarafından yayımlanan ortak yorum kuralları, Deniz Alacaklarına Karşı Mesuliyetin Sınırlanması Hakkında 1976 Tarihli Milletlerarası Sözleşmenin hazırlık çalışmaları, Sözleşmede öngörülen kusur dereceleri ve pervasızca davranışın sigorta sözleşmelerine etkisi de incelenerek değerlendirilmiştir.
Sorumluluk Sınırlarının Kaldırılmasının Yorumlanması ile İlgili Uluslararası Denizcilik Örgütü Kararı
Keywords: Convention on Limitation of Liability for Maritime Claims; 1976; International Convention on Civil Liability for Oil Pollution Damage 1992; IMO’s Common Interpretation Rules; Wilful Misconduct; Alter Ego; Deniz Alacaklarına Karşı Mesuliyetin Sınırlanması Hakkında 1976 Tarihli Milletlerarası Sözleşme; 1992 Petrol Kirliliğinden Doğan Zararın Hukuki Sorumluluğu ile İlgili Milletlerarası Sözleşme; Uluslararası Denizcilik Örgütü Ortak Yorum Kuralları; Pervasızca Davranış; Alter Ego